When the Quarter Jumps into a Cup (and When It Does Not) - Dutra, Mateo (2022)
While Bernoulli’s equation is one of the most frequently mentioned topics in physics literature and other means of dissemination, it is also one of the least understood. Oddly enough, in the wonderful book Turning the World Inside Out, Robert Ehrlich proposes a demonstration that consists of blowing a quarter coin into a cup, incorrectly explained using Bernoulli’s equation. In the present work, we have adapted the demonstration to show situations in which the coin jumps into the cup and others in which it does not, proving that the explanation presented in Ehrlich’s book based on Bernoulli’s equation is flawed. Our demonstration is useful to tackle the common misconception, stemming from the incorrect use of this equation, that higher velocity invariably means lower pressure